Research Trend of Science Process Skills in Prospective Physics Teachers: An Analytical Review - Ate, Ogiarto; Parno, Parno; Munfaridah, Nuril (Berkala Ilmiah Pendidikan Fisika, 2024)
It is imperative to research the science process skills of prospective physics teachers in higher education to improve the quality of physics education, support curriculum development, and enhance student understanding. This study examines the research trends regarding the science process skills of prospective physics teachers in physics education at higher education institutions. The review of journal publications from 2019 to 2023 was conducted using content analysis, a qualitative method. A total of 24 journal articles focusing on the science process skills of prospective physics teachers in higher education were identified through Publish or Perish, using the Google Scholar and Scopus databases between 2019 and 2023. The analysis steps included framing review questions, identifying relevant research, assessing study quality, summarizing evidence, and conducting data analysis. The results showed that research on the science process skills of prospective physics teachers has been prevalent since 2019, with quantitative research dominating the field. Basic physics practicum courses are the primary focus for exploring students' science process skills, with tests being the most commonly used instruments. Several interventions, such as Project-Based Learning (PjBL), STEAM, Discovery, and Inquiry, have been implemented to enhance the science process skills of physics teacher candidates. Communication skills, a component of the 21st-century 4C skills, are particularly pertinent to the future challenges that educators will encounter, as evidenced by the science process skills examined in previous research. These skills are critical in fostering collaboration, problem-solving, and effective teaching. In conclusion, this study emphasizes the importance of developing physics teacher candidates' science process skills, particularly communication skills, in higher education. Future research is expected to deepen the understanding and develop more effective learning strategies to improve these essential skills in physics teacher candidates.